PENGARUH CITRA MEREK DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN MOBIL HONDA JAZZ - Muhammad Jazim Hamidi; Nuraini; Ajat Sudrajat (Jurnal Manajemen Bisnis Krisnadwipayana, 2020)
The purpose of this study to obtain the empirical evidence and to find clarity of phenomena and conclusions about the influence of these two variables above on Car Buying Honda Jazz Decision to consumers Honda Jazz in Karawang. Samples were collected by using Purposive Sampling with a sample of 100 respondents. Data analysis techniques used are Scale Range Analysis and Path Analysis with the help of Method of Successive Interval (MSI), Microsoft Excel 2010 and SPSS 21 computer programs. From the analysis of research data, obtained some conclusions are follows: Honda Jazz Car Image of 393.6 is on criteria Agreed. Quality of Honda Jazz Car Product of 382.2 is on criteria Agreed. Car Buying Honda Jazz decision of 398.53 is on criteria Agreed. There is a partial influence between Brand Image and Product Quality of 0.651. This shows a strong and undirectional relationship because it has a positive value. There is partial influence between Brand Image to Purchase Decision equal to 38.3% and there is partial influence between Product Quality to Purchase Decision equal to 47.3%. There is simultaneous influence between Brand Image and Product Quality on Car Buying Decision of Honda Jazz to consumers in Karawang equal to 60.3%, while the rest are other factors not examined equal to 39.7%.